Ações pedagógicas do professor de piano popular: um estudo de caso - Ana Carolina Nunes do Couto (2008)
This work approaches the pedagogy of popular music in a very specific context:popular piano lessons. The main objective was the investigation of existing approaches of informal music learning in popular piano lessons. The informal learning practices of music are considered by experts as essential to make the repertoire learning authentic. Based on this assumption, an investigation of how the lessons of an instrument traditionally linked to classical music can teach one type of repertoire that has remained for such a long time at the fringes of formal study. To realize this research, seven popular music teachers were interviewed and also their classes were observed, with the objective of collecting passive data for analysis that could signify the attitudes and thoughts of these teachers. This study permitted the verification that, the teachers demonstrated knowledge of the importance to the practice of informal learning for the development of the work with the popular repertoire. Not all practices are used in their lessons, for various reasons, such as limited time in each class, the expectation of the student to receive information from their teachers and in the case of some teachers, thinking still linked to a more traditional lesson model. The study points to the importance that the University has in the promotion and development of research in this area, so that professionals that work with popular piano can justify the usage of certain learning practices, which thus far remain at the fringes of formal music teaching.